Modulation of Adaptive Immunity and Viral Infections by Ion Channels - Bohmwald, Karen; Gálvez, Nicolás M. S.; Andrade, Catalina A.; Mora, Valentina P.; Muñoz, José T.; González, Pablo A.; Riedel, Claudia A.; Kalergis, Alexis M. (Frontiers in Physiology, 2021)
Most cellular processes require that proper ion homeostasis is maintained. Among others, ion channels play a crucial role in controlling the homeostasis of anions and cations concentration between the extracellular and intracellular compartments. Calcium (Ca2+) is one of the most relevant ions implicated in regulating critical functions of immune cells, which allows the appropriate triggering of immune cell responses against pathogens and tumor cells. Due to its importance in inducing the immune response, some viruses have evolved mechanisms to modulate intracellular Ca2+ concentrations and the mobilization of this cation through Ca2+ channels to increase their infectivity and as evasion mechanisms of the immune system. For instance, some viral infections require Ca2+ to enter the cell and their replication and budding. Moreover, through the expression of viral proteins on the surface of infected cells, Ca2+ channels function can be altered, enhancing the pathogen evasion of the adaptive immune response. Here, we review essential aspects of ion concentrations and ion channel function in the context of viral infections and their contribution to the modulation of adaptive immune responses.